2003
DOI: 10.1088/0029-5515/43/9/312
|View full text |Cite
|
Sign up to set email alerts
|

The confinement of dilute populations of beam ions in the national spherical torus experiment

Abstract: Short ∼3 ms pulses of 80 keV deuterium neutrals are injected at three different tangency radii into the national spherical torus experiment. The confinement is studied as a function of tangency radius, plasma current (between 0.4 and 1.0 MA), and toroidal field (between 2.5 and 5.0 kG). The jump in neutron emission during the pulse is used to infer prompt losses of beam ions. In the absence of MHD, the neutron data show the expected dependences on beam angle and plasma current; the average jump in the neutron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 30 publications
4
37
0
Order By: Relevance
“…Because the neutron rate is dominated by beam-plasma reactions, this indicates that a significant fraction of high-energy fast ions are accelerated by the RF heating. The pulses in the neutron rate between 0.17 and 0. analyzed using the technique described in [29]. For each pulse, the neutron emission R n rises nearly linearly during the beam injection, then decays approximately exponentially following the pulse.…”
Section: Neutron Measurementsmentioning
confidence: 99%
“…Because the neutron rate is dominated by beam-plasma reactions, this indicates that a significant fraction of high-energy fast ions are accelerated by the RF heating. The pulses in the neutron rate between 0.17 and 0. analyzed using the technique described in [29]. For each pulse, the neutron emission R n rises nearly linearly during the beam injection, then decays approximately exponentially following the pulse.…”
Section: Neutron Measurementsmentioning
confidence: 99%
“…[9][10][11][12][13][14] Also the slowing-down of a barium ion beam with energy 0-40 eV was measured in a Q-machine in which the quiescent plasma ͑T e Ϸ 0.2 eV͒ is confined by a uniform magnetic field. 15 The changes in velocity ͑due to beam slowing-down͒ agree with the predictions of the Fokker-Planck equation within error bars for different ions at different densities.…”
Section: Introductionmentioning
confidence: 99%
“…Before examining those calculations directly, it is useful to compare measurements and modeling of the neutron evolution before and after a step change in the neutral beam power. Previous experiments have studied the behavior of "dilute" populations of fast ions [32,49,50,74], including studies in NSTX L--mode plasmas [74]. The latter study showed that the prompt loss and slowing down of fast ions in those plasmas were consistent with classical behavior.…”
Section: : Comparison Of the Measured And Simulated Neutron Dynamicsmentioning
confidence: 94%
“…The initial rise of the neutron signal is indicative of the prompt loss rate [74]. The decay of the neutron emission when a beam is turned off is fit to…”
Section: : Comparison Of the Measured And Simulated Neutron Dynamicsmentioning
confidence: 99%